A European update on transcatheter aortic valve implantation (TAVI) in the COVID era. Issue 1 (24th September 2022) - Antony, Ishan; Mehari Abraha, Hyab; Hameed, Aamir; Conway, Claire
Abstract: Minimally invasive approaches for aortic valve replacement are now at the forefront of pathological aortic valve treatment. New trials show comparability of these devices to existing therapies, not only in high‐risk surgical cohorts but also in low‐risk and intermediate‐risk cohorts. This review provides vital clinical and anatomical background to aortic valvular disease treatment guidelines, while also providing an update on transcatheter aortic valve implantation (TAVI) devices in Europe, their interventional trials and associated complications. Abstract : A timely review of key Transcatheter Aortic Valve Implantation (TAVI) device trials delineated by surgical risk.